A Multi-Faceted Approach to Understand How Resource Diversity Can Mediate the Coexistence of Cryptic Marine Nematode Species - Guden, Rodgee Mae; Derycke, Sofie; Moens, Tom (Frontiers in Marine Science, 2021)
Based on the principle of competitive exclusion, species occupying the same ecological niche cannot stably coexist due to strong interspecific competition for resources. Niche diversification, for instance through resource partitioning, may alleviate competition. Here, we investigate the effects of resource diversity on foraging behavior, fitness and interspecific interactions of four cryptic bacterivorous nematode species (Pm I–IV) of the Litoditis marina species complex with sympatric field distributions. Three resource (bacteria) diversity levels (low, medium, high) were used as food treatments and compared to a treatment with only Escherichia coli as food. Differences in taxis to food existed between the cryptic species and between bacterial mixtures of different diversity: all the cryptic species except Pm I showed higher attraction toward medium-diversity food. Furthermore, the cryptic species of L. marina generally exhibited higher fitness on a more diverse food resource. Resource diversity also impacted the interspecific interactions between the cryptic species. Our results show that resource diversity can alter the interspecific interactions among the cryptic species of L. marina, indicating that competitive equilibria between species are very context-dependent. Although a considerable body of evidence supports the hypotheses (e.g., “variance-in-edibility” hypothesis and the “dilution hypothesis” or “resource concentration hypothesis”) which predict a negative impact on consumers when resource diversity is increased, the benefits of a diverse resource can outweigh these disadvantages by offering a more complete and/or complementary range of nutritional resources as suggested by the “balanced diet” hypothesis.